2017
DOI: 10.2147/ppa.s136567
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported outcome assessment of inflammatory arthritis patient experience with intravenously administered biologic therapy

Abstract: ObjectiveTo evaluate patient perspectives regarding utilization of intravenous (IV) therapy for inflammatory arthritis (IA).MethodsThis was a single-center, noninterventional, patient questionnaire-based study of adult IA patients currently receiving IV biologics. At a single visit, patients completed the questionnaire comprising 30 questions centered on their experience receiving an intravenously administered therapy to treat their IA. The questionnaire included questions on patient demographics, disease char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
(9 reference statements)
1
5
0
Order By: Relevance
“…Results of Survey II were also consistent with previous data in the literature regarding patients’ acceptance of IV therapy; Canadian patients with rheumatic diseases surveyed generally reported very favorable perceptions of IV therapy and felt that the time commitment to obtain biologic therapy was highly worthwhile, and perceptions of IV therapy and the associated time commitment improved favorably after receiving multiple infusions in the program.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Results of Survey II were also consistent with previous data in the literature regarding patients’ acceptance of IV therapy; Canadian patients with rheumatic diseases surveyed generally reported very favorable perceptions of IV therapy and felt that the time commitment to obtain biologic therapy was highly worthwhile, and perceptions of IV therapy and the associated time commitment improved favorably after receiving multiple infusions in the program.…”
Section: Discussionsupporting
confidence: 81%
“…The specific disease state also appeared to affect patient preferences for route of administration; IV therapy was preferred by a higher proportion of patients with RA, while SC therapy was preferred by a higher proportion of patients with PsA. In a survey reported recently by Gaylis et al , patients with inflammatory arthritis reported a number of perceived advantages with IV therapy, including additional monitoring by health care staff, the immediate availability of health care resources, less frequent dosing, ease of scheduling administrations, and reduced fear of self‐injection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bolge et al (15) conducted semi-structured telephone interviews with 405 patients receiving IV therapy [including 204 (50.4%) with RA] and found the majority of patients preferred IV medication to SQ injection, with the most common reasons for preference for IV therapy were aversion to self-inject, less frequent dosing, and preference for administration by a health care professional. Gaylis et al (16) performed a single-center, non-interventional patient questionnaire-based study of 100 patients with inflammatory arthritis currently receiving IV biologics, including 31 patients who were previously treated with SQ medications, and similarly found patients had a favorable perception of IV therapy, with 90% patients rating their satisfaction with current IV therapy as 4 or 5 on a 5-point Likert scale. Desplats et al (17) analyzed preferences for switching from IV to SQ in 127 patients treated by tocilizumab and 74 patients by abatacept.…”
Section: Preferences For Dmard Route Of Administrationmentioning
confidence: 99%